STUDI TENTANG ANYAMAN LAPIAK PANDAN DI NAGARI MUARO PINGAI, KECAMATAN JUNJUNG SIRIH KABUPATEN SOLOK - CHYINTIA MELLI SETIADI, Dra. Minarsih, M.Sn, Drs. Erwin, M.Sn (Universitas Negeri Padang, 2015)
This research has a purpose to describe 1) form; 2) function; 3) significance of woven screw pine lapiak woven motif, in order to be known by people both local and outside community. The theory which is used are culture, custom, significance, woven, the elements and principle of art. The source that is taken by the researcher such as: note (recordings, picture) which is gotten from, the informant by doing the interview, documentation, literature study. Motif woven screw pine lapiak comes from flora, fauna, and geometrical, the function of consist of physical, personal and social, in general the meaning of woven screw pine lapiak describes the philosophy of Minangkabau, “Alam Takambang Jadi Guru.”Kata kunci: Motif, Bentuk, Fungsi, Makna